2013
DOI: 10.1534/genetics.113.155135
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Adaptation in Sexuals and Asexuals: A Solvable Model of the Fisher–Muller Effect

Abstract: The adaptation of large asexual populations is hampered by the competition between independently arising beneficial mutations in different individuals, which is known as clonal interference. In classic work, Fisher and Muller proposed that recombination provides an evolutionary advantage in large populations by alleviating this competition. Based on recent progress in quantifying the speed of adaptation in asexual populations undergoing clonal interference, we present a detailed analysis of the Fisher-Muller m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 71 publications
3
19
0
Order By: Relevance
“…They determine the genetic structure of populations and therefore play a central role in many evolutionary and ecological processes (e.g. the rate of adaptation, genetic load or inbreeding depression, Hedrick & Kalinowski, 2000;Haag & Roze, 2007;Gl emin & Ronfort, 2013;Park & Krug, 2013). Parthenogenesis, that is reproduction through unfertilized eggs, is a widespread mode of reproduction in nature (Bell, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…They determine the genetic structure of populations and therefore play a central role in many evolutionary and ecological processes (e.g. the rate of adaptation, genetic load or inbreeding depression, Hedrick & Kalinowski, 2000;Haag & Roze, 2007;Gl emin & Ronfort, 2013;Park & Krug, 2013). Parthenogenesis, that is reproduction through unfertilized eggs, is a widespread mode of reproduction in nature (Bell, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Over time, this experiment has become a model for exploring many other aspects of evolution, including the emergence of new functions (Blount et al 2008), the evolution of mutation rates (Sniegowski et al 1997), the maintenance of genetic diversity (Elena and Lenski 1997;Rozen and Lenski 2000;Le Gac et al 2012), and the structure of the fitness landscape (Khan et al 2011;Woods et al 2011;Wiser et al 2013). The ability to examine these and other issues has grown tremendously as data that were difficult or impossible to obtain when the LTEE began have yielded to new technologies, particularly genome sequencing Lenski 2009, 2013;Blount et al 2012;Wielgoss et al 2013).The LTEE has also inspired theoretical work, especially on the dynamics of adaptation in large asexual populations (Gerrish and Lenski 1998;Hegreness et al 2006;Desai and Fisher 2007;Schiffels et al 2011;Park and Krug 2013;Wiser et al 2013). The LTEE populations are subject to clonal interference, a phenomenon that limits the rate of adaptation by natural selection in large asexual populations.…”
mentioning
confidence: 99%
“…The LTEE has also inspired theoretical work, especially on the dynamics of adaptation in large asexual populations (Gerrish and Lenski 1998;Hegreness et al 2006;Desai and Fisher 2007;Schiffels et al 2011;Park and Krug 2013;Wiser et al 2013). The LTEE populations are subject to clonal interference, a phenomenon that limits the rate of adaptation by natural selection in large asexual populations.…”
mentioning
confidence: 99%
“…Muller (1932, 1964) developed Fisher’s idea and concluded that recombination among many loci could allow a sexual population to evolve “hundreds to millions of times faster” than a comparable asexual population. This same idea of an increasing advantage for recombination as the number of loci under selection increases, has been echoed in later papers (e.g., Crow and Kimura 1965, Otto and Barton 2001, Iles et al 2003, Park and Krug 2013, Edhan et al 2017). Park and Krug (2013) have shown that the advantage of recombination is proportional to L, where L is the number of loci under selection.…”
Section: Discussionmentioning
confidence: 72%
“…This same idea of an increasing advantage for recombination as the number of loci under selection increases, has been echoed in later papers (e.g., Crow and Kimura 1965, Otto and Barton 2001, Iles et al 2003, Park and Krug 2013, Edhan et al 2017). Park and Krug (2013) have shown that the advantage of recombination is proportional to L, where L is the number of loci under selection. Thus, the increasing advantage of sex as the number of loci under selection increases offsets the increasing cost of natural selection that was predicted by Haldane (1957).…”
Section: Discussionmentioning
confidence: 72%